2017
DOI: 10.1002/ijgo.12253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multifaceted postpartum hemorrhage‐management intervention in community hospitals in Southern Thailand

Abstract: Implementation of the multifaceted intervention improved PPH management at community hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, the effect on clinical outcomes was not identified in this study. A significant improvement of active care, particularly in the use of indwelling bladder catheters Original Article SMJ 24 and 2 randomized-controlled trials [25][26] , as well as 3 before-and-after quasi-experimental trials. 20,27,28 Although these studies showed a variation in the outcomes monitored of PPH, the use of multifaceted intervention was a common strategy for preventing PPH and improving its management.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect on clinical outcomes was not identified in this study. A significant improvement of active care, particularly in the use of indwelling bladder catheters Original Article SMJ 24 and 2 randomized-controlled trials [25][26] , as well as 3 before-and-after quasi-experimental trials. 20,27,28 Although these studies showed a variation in the outcomes monitored of PPH, the use of multifaceted intervention was a common strategy for preventing PPH and improving its management.…”
Section: Discussionmentioning
confidence: 99%
“…At maternity level, despite the inconclusive Pithagore-6 cluster RCT 26 , community-based multifaceted interventions, aimed at improving the translation into clinical practices of the guidelines for PPH management, have gained attention in recent years and even proved effectiveness in low-middle income countries. 39 At individual level, oxytocin infusion is mandatory for the prevention of third-stage labour and postpartum bleeding risks. In the presence of PPH, re-administration of oxytocin should be prompt, as it was shown ineffective when performed more than 20 min after onset of PPH to avoid progression towards S-PPH.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have reported a relatively high maternal mortality among the minorities in Thailand [ 17 , 18 ]. Therefore, consideration of local or context-specific risk factors, such as race, ethnicity, socioeconomic status, cultural belief, and accessibility to health care services, might be crucial [ 18 ].…”
Section: Introductionmentioning
confidence: 99%